Analisis Physical Fitness Terhadap Kemampuan Lompat Jauh - Susila, Linda (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2022)
The purpose of the study. To find out how far the influence of physical components (physical fitness) which includes speed, leg explosive power and balance on long jump ability. Materials and methods. This research is descriptive with regression technique which gives a general description about agility, limb explosive power and balance with long jump ability. The research subjects used were 40 people. With a random sampling technique, the data is processed using a correlation technique through the help of the SPSS program. Results. From the data analysis, the results obtained are: (1). There is a significant effect of speed on the long jump ability, with the value of r arithmetic (r0)=0.687 (P<0.05) with a contribution value of 47.2% (2). There is a significant effect of limb explosive power on Long Jump Ability. with a calculated r value (r0) = 0.504 (P<0.05) with a contribution value of 25.4% (3). There is a significant effect on the balance of Long Jump Ability, with a calculated r value (r0) = 0.415 (P<0.05) with a contribution value of 17.2% (4). There is a significant effect together in terms of speed, leg explosive power, balance on Long Jump Ability, with a calculated r value (r0) = 0.725 (P < 0.05) with a contribution value of 52.6%. Conclusions. From the results of data processing, it shows that it has a significant influence from data analysis, namely speed, leg explosive power and balance on long jump ability